The innovation inducement impact of environmental regulations on maritime transport: A literature review - Teemu Makkonen; Sari Repka (Inderscience Publishers, 2022)
Maritime transport is facing wide-ranking challenges due to stricter environmental regulations. It has been positioned that these stricter environmental regulations will significantly hamper the competitiveness of the shipping industry and other export/import oriented industries. However, contrasting views, arguing that environmental regulations will, in fact, enhance firms competitiveness by inducing innovation, have also been voiced. Here this issue is examined through a literature review on the innovation inducement impact of environmental regulations (i.e. the Porter Hypothesis), in general, and the economic impacts of environmental regulations (here Annex VI of the MARPOL Convention) as it applies to shipping in Northern Europe, in particular. According to the review, the literature is still inconclusive and lacks a clear consensus on the economic and innovation inducement impacts of environmental regulations on maritime transport. Therefore, the review concludes in suggestions for further studies on the use of marine scrubber systems as an illustrative case study example.